Features of New Blue-Green Types for the Adjacent Lakes of the Mezhdurchechina Reservoir - Alimjanova Kholiskhon Alimjanovna; Elmuratova Aygul Almuratovna (Zien Journals, 2022)
The article presents the results of a study (2003-2021) of the composition of algae in the Mezhdurechinsky reservoir. The average content of dissolved oxygen, bicarbonates, sulfate ions of chlorides and other metals in the water of the reservoir was determined. The water mineralization of lakes Koshpeli Aidyn, Autel and Baltaketken is maximum within the reservoir and ranges from 2500.3 to 4372.6 mg/l. Of the biogenic elements in the water of the reservoir, the readings of silicon, iron, phosphates, nitrates, and ammonium were determined.
Keywords: Blue-green; biodiversity; analysis; biogenic element